KOMPOSISI VEGETASI DAN POTENSI PEMANFAATAN GULMA DI LAHAN PERTANAMAN SEMANGKA KEBUN INOVASI POLITEKNIK NEGERI JEMBER - Sumarlina, Sumarlina; Napitupulu, Tia Sofiani; Husnudin, Uni; Lestari, Datik; Krismiratsih, Fitri (Biospecies, 2026)
Kebun Inovasi is one of the teaching factories at Politeknik Negeri Jember (Polije) that produces various food and horticultural crops sustainably, including watermelon. However, observations showed a high abundance of weeds growing in the watermelon cultivation areas. Therefore, this study aimed to determine the vegetation composition and utilization potential of weeds in the watermelon cultivation areas at Kebun Inovasi Polije to support appropriate weed management planning. Sampling was conducted using a purposive sampling technique with the quadrat method. A total of ten plots (1 × 1 m) were established in areas with weed vegetation. Weed identification was carried out based on morphological characteristics and relevant literature. The results showed that 17 weed species belonging to 13 families were found, with a moderate species diversity index. Torenia crustacea was identified as the most dominant species. The identified weed species have potential uses in the fields of health, environmental management, and industry.